Anti-money laundering and know your customer - Indian Institute of Banking & Finance; Indian Institute of Banking & Finance (New Delhi : Macmillan, 2010)
The book provides the theoretical background on the subject and practical steps for banks implementing Anti-Money Laundering/Know Your Customer (AML/KYC) regime in accordance with international standards. It explains the basic elements required to build an effective AML/KYC framework and summarizes the role of the employees in fighting money laundering. It also contains the Guidance Notes for banks on AML and KYC issued by the Indian Banks' Association.
nif 17/05/13
Loan
Keywords: Banks and banking -- Accounting; Money Laundering -- Prevention